2007
DOI: 10.1086/512372
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Naturally Acquired Inhalation Anthrax: Clinical Care and Analyses of Anti-Protective Antigen Immunoglobulin G and Lethal Factor

Abstract: This report describes the first case of naturally acquired inhalation anthrax in the United States since 1976. The patient's clinical course included adjunctive treatment with human anthrax immunoglobulin. Clinical correlation of serologic assays for the lethal factor component of lethal toxin and anti-protective antigen immunoglobulin G are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 7 publications
3
94
0
1
Order By: Relevance
“…Using a highly sensitive assay for detection of LF activity, Boyer et al found that LF in the serum of infected macaques exhibited a triphasic kinetic profile, increasing with time after infection (41). By using the same method to monitor LF concentrations in the plasma of a human patient with naturally acquired anthrax, LF levels were highest (294.30 ng/ml) in the initial 24 h and remained detectable after the clearance of bacilli with antibiotic treatment (42). The interplay between the expression of InhA1 and LF in vivo may be important for the progression of anthrax disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using a highly sensitive assay for detection of LF activity, Boyer et al found that LF in the serum of infected macaques exhibited a triphasic kinetic profile, increasing with time after infection (41). By using the same method to monitor LF concentrations in the plasma of a human patient with naturally acquired anthrax, LF levels were highest (294.30 ng/ml) in the initial 24 h and remained detectable after the clearance of bacilli with antibiotic treatment (42). The interplay between the expression of InhA1 and LF in vivo may be important for the progression of anthrax disease.…”
Section: Discussionmentioning
confidence: 99%
“…Once patients display symptoms of inhalational anthrax, unfortunately, the infection has generally progressed to a point where even effective bactericidal antibiotic treatment can save only 55% of the infected individuals (8). This "point of no return" may reflect the fact that infection has progressed so far as to have disseminated from the original site of infection and spread hematogenously into the lungs and mediastinum to cause the classical diagnostic mediastinal widening associated with advanced inhalational anthrax, a point where it has been suggested that enough total exotoxin has been released to kill the host even in the absence of viable bacteria (73). This idea has some historical precedent, having first been proposed in 1924 by Fraenkel, who proposed that the initiating site of infection was in the tracheo-bronchial mucosa and that pneumonia developed after infection had been established (23).…”
Section: Reforming the Trojan Horse Model In Light Of New Datamentioning
confidence: 99%
“…Studies of adaptive immunity to anthrax infection have focused overwhelmingly on serology, with only one study reporting T cell responses to PA (10)(11)(12)(13). Data from animal or human vaccination studies show that the induction of LT-neutralizing Ab by vaccines containing PA correlates with protection (14)(15)(16).…”
mentioning
confidence: 99%